2020
DOI: 10.1515/hf-2019-0182
|View full text |Cite
|
Sign up to set email alerts
|

Violin varnish induced changes in the vibro-mechanical properties of spruce and maple wood

Abstract: Violin varnishes are known to alter the longitudinal and radial material properties of violin tonewood. Here, the varnish-induced changes in the vibrational and elastic properties of spruce and maple wood were studied by modal analysis of rectangular plates. This contact-free investigation yields the eigenfrequencies and corresponding mode shapes and modal damping ratios of multiple out-of-plane modes. The longitudinal and radial E-modulus and the in-plane shear modulus were determined by an inverse material p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…rough market research, we found that most of the musical instrument education software in the market focuses on providing learners with musical instrument teaching videos, or through the video function of mobile phones, real-time transmission of the fingering, and instrument pronunciation of the practitioners to the musical instrument teachers, so as to realize the accompaniment and remote guidance of musical instrument learning [3].…”
Section: Introductionmentioning
confidence: 99%
“…rough market research, we found that most of the musical instrument education software in the market focuses on providing learners with musical instrument teaching videos, or through the video function of mobile phones, real-time transmission of the fingering, and instrument pronunciation of the practitioners to the musical instrument teachers, so as to realize the accompaniment and remote guidance of musical instrument learning [3].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these considerations, currently, the most well-known types of varnishes used for maestro- and professional-level musical instruments are those with an oil-based solvent and those with an alcoholic solvent (spirit) [ 32 , 33 , 34 , 35 ]. Not only is the chemical composition of the surface treatment important but also the thickness of the varnish film and the varnish–wood interface, aspects highlighted in studies [ 36 , 37 , 38 ]. The type of varnish and its thickness correlated with the number of layers applied in the finishing process influence the tonality of the musical instrument as a result of not only the difference in stiffness between the wood and the varnish film but also as an effect of the increase in the mass of the layered material (wood–varnish) [ 31 , 32 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to [ 36 , 38 ], to compare the mass changes of the spruce and maple boards before and after surface treatments (VS varnish system, UV exposure, and salt fog exposure), the changes were evaluated as area mass loading (AML) calculated based on mathematical relation (1): where is area mass loading induced by treatment (g·m −2 ); —the final mass of the treated wood; —the initial mass of the wooden sample; b —the width of the plate; and l —length of the plate [ 36 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the research carried out by refs. [13][14][15][16] highlighted that both: the type of varnish (resin type) and especially the number of layers (film thickness) are responsible for the change in the acoustic quality of a violin, either ennobling or affecting the quality it had before being varnished. The argument of these researchers is related to the surface and mechanical changes that occur as a result of applying the varnish films, and on the other hand, the changes in the porosity and surface roughness of wood, as well as the increase in mass, stiffness and internal friction of the new system (varnish film and wood).…”
Section: Introductionmentioning
confidence: 99%